2013
DOI: 10.1007/s10439-013-0801-y
|View full text |Cite
|
Sign up to set email alerts
|

An Instrumented Mouthguard for Measuring Linear and Angular Head Impact Kinematics in American Football

Abstract: The purpose of this study was to evaluate a novel instrumented mouthguard as a research device for measuring head impact kinematics. To evaluate kinematic accuracy, laboratory impact testing was performed at sites on the helmet and facemask for determining how closely instrumented mouthguard data matched data from an anthropomorphic test device. Laboratory testing results showed that peak linear acceleration (r2 = 0.96), peak angular acceleration (r2 = 0.89), and peak angular velocity (r2 = 0.98) measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
203
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(209 citation statements)
references
References 26 publications
6
203
0
Order By: Relevance
“…The striking uniformity of impacts oscillating around 20 Hz indicates that a substantial portion of sports head impacts are exciting a mechanical resonance of the skull-brain system and causing amplified skull-brain relative motions. In previous studies using our instrumented mouthguard, we showed that the natural frequency of the mouthguard is around 150 Hz and that head impacts had much higher energy levels at lower frequencies, suggesting that the measured frequency content has not been biased by the instrumentation [30,32]. The above information again prompts the long-ignored question: can mechanical resonance lead to mTBI?…”
Section: Discussionsupporting
confidence: 62%
“…The striking uniformity of impacts oscillating around 20 Hz indicates that a substantial portion of sports head impacts are exciting a mechanical resonance of the skull-brain system and causing amplified skull-brain relative motions. In previous studies using our instrumented mouthguard, we showed that the natural frequency of the mouthguard is around 150 Hz and that head impacts had much higher energy levels at lower frequencies, suggesting that the measured frequency content has not been biased by the instrumentation [30,32]. The above information again prompts the long-ignored question: can mechanical resonance lead to mTBI?…”
Section: Discussionsupporting
confidence: 62%
“…5,12 Head impact kinematics in contact sports are investigated using the Head Impact Telemetry system 13,14 and accelerometerembedded mouthguards. 15,16 However, there are substantial knowledge gaps in the relationships between subconcussive impact kinematics and outcome measures. The ocular-motor system orchestrates accommodation and vergence, and their concomitant adjustments enable individuals to visualize an object at various distances and directions.…”
Section: Invited Commentarymentioning
confidence: 99%
“…50,51 Linear acceleration, a lin , was not used here because a lin -induced brain strain responses are negligible because of the near incompressibility of the brain. This was confirmed in terms of both maximum principal strain, e ep (using DHIM and an independently developed head model, SIMon 36 ), and WM fiber strain, e n: :…”
Section: Idealized Head Impactsmentioning
confidence: 99%
“…In addition, a pre-computation strategy may also be effective in the context of contact sports, 32,46 because the head's impact temporal characteristics appear largely similar within or across subjects. 50,51 On the other hand, when using realistic head impacts as model inputs, tract-specific injury susceptibility indices could allow assessment of the relative injury vulnerabilities of neural pathways to identify the most vulnerable ones in real-world injury scenarios. These will be the subjects of future investigations.…”
mentioning
confidence: 99%